Management of Gender Equality: Semiotics of All-Gender Restrooms - Saengmaneedech, Dr.Thirawut; Sompongcharoen, Dr.Chaowalit; Thammawimutti, Dr.Apiluck; Chinachot, Dr.Pirun; Pemchart, Dr.Nongluck; Khamlert, Apichet (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2024)
This academic article aimed 1) to study the semiotics of all-gender restrooms in public places and 2) to study the obstacles and problems of the Thai government in providing all-gender restroom services in public places. Sexual orientation represented the behaviors related to an individual’s thoughts, beliefs, and attitudes towards sexual orientation, expression and satisfaction upon on the individual’s society and culture. It was also believed that the individual’s sexual orientation or gender is not limited to only male and female. Meanwhile, achieving gender equality was regarded as a sustainable development goal for social progress and development. Individuals of all genders should be given with equal rights, freedoms, and opportunities to access public services. However, public restrooms in Thailand were separated based on sex assigned at birth, resulting in several gender inequality issues. The appropriate solution was to provide all-gender restrooms, which many countries had piloted to provide them in public places. The Thai government was still required to further study the ways to solve and reduce the risk of sexual harassment in all-gender restrooms along with shaping a positive perception and attitude among service users towards all-gender restrooms in order to make them use these restrooms more.